Evaluation of the Effectiveness of Telehealth Chronic Disease Management System: Systematic Review and Meta-analysis - Ziyan Xiao; Xiuping Han (JMIR Publications, 2023)
BackgroundLong-term daily health monitoring and management play a more significant role in telehealth management systems nowadays, which require evaluation indicators to present patients' general health conditions and become applicable to multiple chronic diseases. ObjectiveThis study aims to evaluate the effectiveness of subjective indicators of telehealth chronic disease management system (TCDMS). MethodsWe selected Web of Science, ScienceDirect, Scopus, Cochrane library, IEEE, and Chinese National Knowledge Infrastructure and Wanfang, a Chinese medical database, and searched papers published from January 1, 2015, to July 1, 2022, regarding randomized controlled trials on the effectiveness of the telehealth system on patients with chronic diseases. The narrative review summarized the questionnaire indicators presented in the selected studies. In the meta-analysis, Mean Difference (MD) and Standardized Mean Difference (SMD) with a 95% CI were pooled depending on whether the measurements were the same. Subgroup analysis was conducted if the heterogeneity was significant, and the number of studies was sufficient. ResultsTwenty RCTs with 4153 patients were included in the qualitative review. Seventeen different questionnaire-based outcomes were found, within which quality of life, psychological well-being (including depression, anxiety, and fatigue), self-management, self-efficacy, and medical adherence were most frequently used. Ten RCTs with 2095 patients remained in meta-analysis. Compared to usual care, telehealth system can significantly improve the quality of life (SMD 0.44; 95% CI 0.16-0.73; P=.002), whereas no significant effects were found on depression (SMD −0.25; 95% CI −0.72 to 0.23; P=.30), anxiety (SMD −0.10; 95% CI −0.27 to 0.07; P=.71), fatigue (SMD −0.36; 95% CI −1.06 to 0.34; P<.001), and self-care (SMD 0.77; 95% CI −0.28-1.81; P<.001). In the subdomains of quality of life, telehealth statistically significantly improved physical functioning (SMD 0.15; 95% CI 0.02 to 0.29; P=.03), mental functioning (SMD 0.37; 95% CI 0.13-0.60; P=.002), and social functioning (SMD 0.64; 95% CI 0.00-1.29; P=.05), while there was no difference on cognitive functioning (MD 8.31; 95% CI −7.33 to 23.95; P=.30) and role functioning (MD 5.30; 95% CI −7.80 to 18.39; P=.43). ConclusionsTCDMS positively affected patients' physical, mental, and social quality of life across multiple chronic diseases. However, no significant difference was found in depression, anxiety, fatigue, and self-care. Subjective questionnaires had the potential ability to evaluate the effectiveness of long-term telehealth monitoring and management. However, further well-designed experiments are warranted to validate TCDMS's effects on subjective outcomes, especially when tested among different chronically ill groups.